L12 Developing A Psychiatric Service For Individuals With Huntington's Disease. (17th September 2014) - Hoblyn, J; Higgins, A; McCaffrey, S; Gallagher, A; O'Neill, S; Ennis, A
Abstract : Background: There are approximately 750 individuals in the Republic of Ireland with HD and 1, 500 others may be at risk. Currently there is no national program of psychiatric care for these individuals. Stigma attached to this disorder may impede contact with services until a crisis develops. History: The Huntington's disease Association of Ireland (HDAI) is a 2-person organisation supporting all. Community Health services include Primary Care and Mental Health Teams who may have limited experience caring for the complex needs of those with HD. There are several Neurologists caring for individuals with HD. Those needing respite or long-term care may be admitted to Nursing Homes. Bloomfield is a 114 bedded Psychiatric Teaching Hospital based on the Quaker ethos. Having several individuals with us who have HD we decided to develop a more comprehensive and holistic service. The Interdisciplinary Team was developed and additional expertise was sought from Speech and Language services, Dietetics, and Neurology. Team Members travelled to the United Kingdom and Northern Ireland to liaise with other services and to access specific trainings. Memory Clinic and Day Centre services started in 2013. Caregiver Workshops were developed to provide support. Sixteen week short stay assessments and long stay care beds are provided. An early intervention Mental Health Support Toolbox for those who have been recently diagnosed with HD is being developed. This is in close collaboration with the HDAI and colleagues in Neurology. Conclusions: Voluntary services can be developed to augment traditional sectors providing psychiatric care for those with HD.